2000
DOI: 10.1164/ajrccm.161.6.9907025
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Airway Inflammation and Remodeling in Ski Athletes with and without Bronchial Hyperresponsiveness to Methacholine

Abstract: Asthma-like symptoms, methacholine hyperresponsiveness, and use of asthma medication are prevalent in elite cross-country skiers. We quantitated mucosal inflammatory cell infiltration and tenascin expression in the subepithelial basement membrane in endobronchial biopsy specimens of the proximal airways from 40 elite, competitive skiers (mean: 17.5; range: 16 to 20 yr) without a diagnosis of asthma, in 12 subjects with mild asthma, and in 12 healthy controls, through immunohistochemistry and indirect immunoflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
261
0
11

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(287 citation statements)
references
References 22 publications
15
261
0
11
Order By: Relevance
“…In contrast with asthmatics, the increased numbers of inflammatory cells in healthy athletes' airways do not correlate with exercise-induced symptoms or bronchial responsiveness [28]. Recently, it has been observed that healthy children undertaking outdoor recreational activities exhibit a significant increase in eNO, dependent on ambient ozone levels, but with no changes in lung function test results [29].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with asthmatics, the increased numbers of inflammatory cells in healthy athletes' airways do not correlate with exercise-induced symptoms or bronchial responsiveness [28]. Recently, it has been observed that healthy children undertaking outdoor recreational activities exhibit a significant increase in eNO, dependent on ambient ozone levels, but with no changes in lung function test results [29].…”
Section: Discussionmentioning
confidence: 99%
“…Thickening of epithelial basement membrane has been observed as a characteristic remodeling for asthma for a long time but was also found in early asthma (Karjalainen et al 2000(Karjalainen et al , 2003. Thickening of basement membrane observed with microscopy correspond to the deposition of extracellular matrix (ECM) at subepithelial space observed by electron microscopy, and it is called subepithelial fibrosis (Roche et al 1989;Jeffery et al 1992).…”
Section: Thickening Of Epithelial Basement Membrane and Subepithelialmentioning
confidence: 99%
“…Indeed, a high prevalence of respiratory symptoms and airway hyperresponsiveness has been found in skiers, swimmers and long-distance runners (75). Endobronchial biopsies of elite, competitive skiers demonstrate elevated numbers of clustered lymphocytes, neutrophils and macrophages (76,77). The increased expression of tenascin possibly reflects ongoing healing and repair processes and remodeling of the airways (77).…”
Section: Cold Air-provoked Long-term Responsesmentioning
confidence: 99%
“…Endobronchial biopsies of elite, competitive skiers demonstrate elevated numbers of clustered lymphocytes, neutrophils and macrophages (76,77). The increased expression of tenascin possibly reflects ongoing healing and repair processes and remodeling of the airways (77). The mucosal cellular infiltrate in the skiers' airways differs from that in asthma, with a greater number of neutrophils and a lesser number of eosinophils, mast cells and macrophages (77).…”
Section: Cold Air-provoked Long-term Responsesmentioning
confidence: 99%
See 1 more Smart Citation